THE ROLE OF THE SOCIAL WORKER IN DEVELOPING CHILDREN’S INDEPENDENCE IN COMMUNITY CARE HOMES - Virbalienė, Rita; Čižikienė, Janina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
This article analyzes the role of social workers in developing children's independence in community care homes. The primary goal of a social worker's activity is to provide a suitable service and teach the recipients of their services to solve problems on their own. The children's opportunity to see and grow up in a close family environment depends on the employees' value orientation and worldview. During the deinstitutionalization processes in Lithuania, social workers had to create an environment close to the family and consolidate the family model in communal children's care homes. This article aims to examine how the training and competencies of social workers impact the preparation of children for independent living in society. Applied research methods are analysis of scientific literature and documents, expert interviews, analysis, and interpretation of research results. The review of the scientific literature, presented in the article and the research data, can be applied to improve community care homes providing social services to highlight the role of social workers in creating a safe environment for the child, involving the child in the planning and organization of activities, fostering self-confidence and their abilities.